Traditional Models of Zakat Management in Rural Communities in Mandailing Natal Regency: A Qualitative Study of Social Awareness and Distribution Effectiveness - Nasution, Martua; Hamid, Asrul (Jurnal Iqtisaduna, 2025)
This study aims to conduct an in-depth analysis of the practices of zakat management and distribution among rural communities in Mandailing Natal, as a representation of traditional zakat patterns in rural areas. The research employs a descriptive qualitative method with a field study approach, utilizing in-depth interviews and direct observation. The findings reveal that although the level of public awareness in fulfilling zakat obligations is relatively high, the understanding of sharia principles such as nishab (minimum threshold), haul (zakat maturity period), and zakat rates remains low. As a result, zakat is often given in ways that do not align with fiqh (Islamic jurisprudence). Zakat management is carried out conventionally without the involvement of formal institutions, and its distribution tends to be consumptive, without addressing the economic empowerment of the mustahiq (eligible zakat recipients). This study recommends strengthening zakat institutions at the village level, enhancing literacy in zakat fiqh, and implementing productive zakat distribution models to optimize the social function of zakat.